Investigation of the Effect of Gammaoryzanol Addition on the Properties of the Nanoliposomes by using Response Surface Methodology: Preparation, Characterization and Optimization: Gammaoryzanol-Loaded Nanoliposomes - Esmaeli, Tayebeh; Ghanbarzadeh, Saeed; Barati, Maedeh; Tila, Dena (Iranian Journal of Pharmaceutical Sciences, 2018)
Liposomes are the most important lipid-based nanocarriers which are used for encapsulation of both hydrophilic and hydrophobic active compounds. The aim of the present study was to investigate the effect of addition of Gammaoryzanol (GO) in the lipid bilayer formulation on the liposomes characteristics prepared by a modified ethanol injection method. GO bearing nanoliposomes were prepared with different phosphatidylcholine (PC): GO molar ratios, which were selected as the independent variables. Subsequently, the particle size (PS), encapsulation efficiency percent (EE%), and drug release over 24 h (D24h), which were considered as dependent variables, were analyzed and optimized by employing response surface methodology (RSM). Graphical response surface and contour plots were drown to understand the interaction effects of different variables. Finally, the optimum points for the variables levels were obtained from the optimization plot. The mean PS, EE% and D24h of Celecoxib-loaded nanoliposomes were found as 102.6 ± 9.5 nm, 67.6 ± 11.2 %, and 53.97 ± 9.6 %, respectively. The results indicated that both PC: GO and PC: Drug ratio were the important contributing variables for PS, and EE% of nanoliposomes; however, only PC: GO had effect on D24h (P<0.05). The optimum formulation of Celecoxib nanoliposomes, where PC: GO and PC: Drug ratio were 4.6 and 3, have PS = 102 nm, EE% = 74.2 % and D24h = 59.9 %. In conclusion, addition of GO and using ethanol injection method besides RSM techniques presented a simple, rapid, and beneficial approaches for preparation of nanoliposomes with optimum characteristics.